2015
DOI: 10.4317/jced.52521
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of a novel cad-cam polymer-infiltrated-ceramic-network

Abstract: Background The field of dental ceramics for CAD-CAM is enriched with a new innovative material composition having a porous three-dimensional structure of feldspathic ceramic infiltrated with acrylic resins.The aim of this study is to determine the mechanical properties of Polymer-Infiltrated-Ceramic-Network (PICN) and compare its performance with other ceramics and a nano-ceramic resin available for CAD-CAM systems. Material and Methods In this study a total of five different materials for CAD-CAM were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
92
1
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 14 publications
16
92
1
7
Order By: Relevance
“…In our study, the highest fracture strength of endocrowns were observed in TZI group (533.61 N for S, 610.54 N for L) which has the highest elasticity moduli and flexural strength, and the lowest values were found in VM2 (47.29 N for S, 71.38 N for L) groups, in accordance with the literatures by Leung et al 40) and Albero et al 41) . The reason for lower fracture strength values obtained in our study for all groups could be attributed to the differences in crown shape (incisor instead of molar) and the force axis (45 degrees angle instead of 90 degrees angle) used in this study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, the highest fracture strength of endocrowns were observed in TZI group (533.61 N for S, 610.54 N for L) which has the highest elasticity moduli and flexural strength, and the lowest values were found in VM2 (47.29 N for S, 71.38 N for L) groups, in accordance with the literatures by Leung et al 40) and Albero et al 41) . The reason for lower fracture strength values obtained in our study for all groups could be attributed to the differences in crown shape (incisor instead of molar) and the force axis (45 degrees angle instead of 90 degrees angle) used in this study.…”
Section: Discussionsupporting
confidence: 81%
“…The study which compared the mechanical properties of feldspathic ceramic (Vita Mark II), lithium disilicate reinforced glass ceramic (IPS e.max CAD) and polymer infiltrated ceramic (Vita Enamic) by three-point bending test, reported that lower flexural strength values were found for feldspathic ceramic (106.67±18.50 MPa) with respect to lithium disilicate reinforced glass ceramic (341.88±40.25 MPa) and polymer infiltrated ceramic (145.95±12.65 MPa) 40) . Similarly, Albero et al 41) reported that feldspathic ceramic (Vita Mark II) provided lower fracture strength values with respect to lithium disilicate reinforced glass ceramic (IPS e.max CAD), polymer infiltrated ceramic (Vita Enamic) and resin-ceramic (LAVA Ultimate). There are some studies which examine the performance of ceramic materials for endocrown restorations in terms of fracture strength.…”
Section: Discussionmentioning
confidence: 99%
“…58,63 Typical ceramic materials have a higher elastic modulus values than PICN 64 . The Vickers hardness of human enamel (3.43 ± 0.16 GPa) and PICN (3.31 ± 0.11 GPa) are similar, 54,65,66,67 and both are higher than the hardness reported for resin composites (0.73 GPa to 1.60 GPa), 68,69 and lower than the hardness of zirconia (13.94 GPa) 70 and lithium disilicate glass ceramics (10.0 GPa to 11.31 GPa). 71 The flexural strength of Enamic (130 MPa) 56 is lower than that of a reference lithium disilicate glassceramic material, IPS e.max (342 MPa).…”
Section: Polymer Infiltrated Ceramic Network (Picns)mentioning
confidence: 88%
“…3,5,6 Within these materials, Lava Ultimate (3M ESPE, St. Paul, MN, USA) is a nanoceramic resin that is composed of nanoceramic particles embedded in a highly cross-linked resin matrix, 3,4 and Vita Enamic (VITA Zahnfabrik, Bäd Sackingen, Germany) is a polymer-infiltrated ceramic network that consists of a feldspar ceramic network infiltrated with a dimetacrylate polymer network. 7,8 An additional material that became available for CAD/CAM technology is Vita Suprinity (VITA Zahnfabrik, Bäd Sackingen, Germany). This material consists of a zirconiareinforced lithium silicate ceramic that supports a wide range of applications, and after crystallization, exhibits higher mechanical properties.…”
Section: Introductionmentioning
confidence: 99%